THE IMPACT OF TIKTOK ON CONSUMER IMPULSIVE BUYING BEHAVIOUR AND CUSTOMER SATISFACTION TOWARDS LOCAL FASHION BRANDS - Istiqomah, Fadhilah
Social media and its impact on consumers' impulsive buying behavior and customer satisfaction have been extensively discussed by journals, but there are gaps in the literature that exist in terms of the social media platform, industry, research location, and variables discussed. External factors (social media marketing, electronic word-of-mouth, and media entertainment) and internal factors (hedonic motivation and trust) have a significant influence on impulsive buying behavior, according to previous research. With these external and internal factors as impulsive buying behavior dimensions, this study aims to fill research gaps by examining the impacts of TikTok and how it influences the consumer impulsive buying behavior on local fashion brands, as well as its effect on customer satisfaction as a post-purchase effect. This research employs a quantitative methodology, using an online survey technique. Respondents who were involved in this study are 260 respondents. Those data were analyzed by the PLS-SEM method using the SmartPLS application. This study's findings reveal that electronic word-of-mouth, hedonic motivation, and trust are variables that influence impulsive buying behavior, and that impulsive buying behavior is also a factor that influences customer satisfaction. According to this research, neither social media marketing nor media entertainment had a positive impact on impulsive buying. This study fills in research gaps and expands our knowledge of the influence of TikTok on impulsive buying behavior and customer satisfaction with the outcomes achieved.